Modulating TICT to ICT characteristics of acid switchable red emitting boradiazaindacene chromophores: Perspectives from synthesis, photophysical, hyperpolarizability and TD-DFT studies. (January 2017) - Thorat, Kishor G.; Ray, Alok K.; Sekar, Nagaiyan
Abstract: Two new red emitting difluoro-boradiazaindacene fluorophores have been synthesized, and their photophysical and hyperpolarizability properties in various microenvironments were evaluated experimentally and characterized in detail with respect to DFT and TD-DFT using B3LYP/6-31G(d) level of theory. The dyes possess reasonable first order hyperpolarizabilities in solvents of different polarities. The photophysical properties of the difluoro-boradiazaindacene cores are found to be highly sensitive towards change in polarity of microenvironments because of twisted intramolecular charge transfer (TICT) characteristics. The dyes show unusually very large Stokes shifts and their photophysical properties such as emission maxima and fluorescence intensity were altered to a great extent in the presence of trace amount of TFA in chloroform. These dyes can be used as promising candidates for pH probes and non-linear optical materials. Graphical abstract: Highlights: Two novel red emitting BODIPY dyes with a large Stokes shift are reported. The dyes are sensitive towards acid and polarity of microenvironments. Fluorophores shows TICT on-off characteristics. These fluorophores can be used as potential pH probes. The dyes possess high values of βCT thus can be used as promising NLO materials.